Efficient chromosomal transposition of a Tc1/mariner- like transposon Sleeping Beauty in mice - Horie, Kyoji (The National Academy of Sciences, 2001)
The presence of mouse embryonic stem (ES) cells makes the mouse a powerful model organism for reverse genetics, gene function study through mutagenesis of specific genes. In contrast, forward genetics, identification of mutated genes responsible for specific phenotypes, has an advantage to uncover novel pathways and unknown genes because no a priori assumptions are made about the mutated genes. However, it has been hampered in mice because of the lack of a system in which a large-scale mutagenesis and subsequent isolation of mutated genes can be performed efficiently. Here, we demonstrate the efficient chromosomal transposition of a Tc1/mariner-like transposon, Sleeping Beauty, in mice. This system allows germ-line mutagenesis in vivo and will facilitate certain aspects of phenotype-driven genetic screening in mice.